Improved biological behaviours and osteoinductive capacity of the gelatin nanofibers while composites with GO/MgO. (3rd February 2022) - Mahdavi, Mohammad Reza; Kehtari, Mousa; Mellati, Amir; Mansour, Reyhaneh Nassiri; Mahdavi, Mehrad; Mahdavi, Mahan; Enderami, Seyed Ehsan
Abstract : Among the many polymers introduced for bone tissue engineering, natural polymers have more advantages due to their high biocompatibility and biodegradability, despite their low mechanical properties. Herein, gelatin nanofibers with and without magnesium oxide (MgO) and graphene oxide (GO) nanoparticles were fabricated by electrospinning. The fabricated gelatin and gelatin/GO/MgO nanofibers were examined using scanning electron microscopy, protein adsorption, cell attachment and viability assays. The results revealed that biological behaviours of the gelatin nanofibers significantly improved while incorporated with MgO and GO nanoparticles. In the following, osteosupportive capacity of the fabricated scaffolds was investigated by Alizarin‐red staining, alkaline phosphatase activity, and calcium content, and bone‐related gene and protein assays. The results revealed that the highest osteogenic differentiation potential of human‐induced pluripotent stem cells (hiPSCs) was detected while these cells were cultured on the gelatin/GO/MgO nanofibers. However, these makers in the hiPSCs cultured on the gelatin nanofibers were also significantly increased in comparison with the cells cultured on the tissue culture plates as a control. In conclusion, the results revealed that predictable disadvantages in gelatin nanofibers can be greatly improved by the addition of MgO and GO nanoparticles, and the resulting composite scaffold could be a potential candidate for use in bone tissue engineering.